Bioavailable IGF-1 and its Relation to the Metabolic Syndrome in a Bi-Ethnic Population of Men and Women - Koegelenberg, A. S. E.; Schutte, R.; Smith, W.; Schutte, A. E. (Hormone and Metabolic Research, 2016)
Insulin-like growth factor 1 (IGF-1), an insulin sensitivity and vasculoprotective factor, associates negatively with the metabolic syndrome. However, IGF-1 is reduced by factors such as inflammation, oxidative stress and liver dysfunction. We investigated the relationship between bioavailable IGF-1 and the number of metabolic syndrome components and determined whether this relationship is independent of inflammation, oxidative stress and gamma glutamyl transferase (γ-GT; a marker of liver dysfunction). This study included 907 black and white participants stratified by sex (aged 43.0±11.8 years). Among them 63 participants had fasting glucose levels of ≥+7.0+mmol/l and/or used diabetes medication. Via standard methods we determined waist circumference, fasting glucose, triglycerides, high-density lipoprotein cholesterol and blood pressure. We also determined high-sensitivity C-reactive protein (CRP), reactive oxygen species (ROS), γ-GT, IGF-1 and insulin-like growth factor binding protein 3 (IGFBP-3). IGF-1/IGFBP-3 was used as an estimate of bioavailable IGF-1. Total IGF-1 was similar between men and women (p=0.10), however, bioavailable IGF-1 was lower in women (p<0.001). In multivariate-adjusted analyses, IGF-1/IGFBP-3 was inversely associated with the number of metabolic syndrome components in both sexes (men: β=− 0.11; p=0.013 and women: β=− 0.17; p=0.003). Upon inclusion of ROS, γ-GT and CRP, significance was lost. In patients without diabetes, the results for men changed marginally, but were consistent for women. We found an inverse association between bioavailable IGF-1 and the number of metabolic syndrome components. But the relationship was dependent on oxidative stress, liver dysfunction and inflammation, suggesting underlying processes by which the metabolic syndrome attenuates IGF-1.
Keywords: metabolic syndrome; insulin-like growth factor binding protein-3; inflammation; oxidative stress; γ-glutamyltransferase